2018
DOI: 10.1038/s41598-017-17436-5
|View full text |Cite|
|
Sign up to set email alerts
|

Differentiated surface fungal communities at point of harvest on apple fruits from rural and peri-urban orchards

Abstract: The diverse fungal communities that colonize fruit surfaces are closely associated with fruit development, preservation and quality control. However, the overall fungi adhering to the fruit surface and the inference of environmental factors are still unknown. Here, we characterized the fungal signatures on apple surfaces by sequencing internal transcribed spacer 1 (ITS1) region. We collected the surface fungal communities from apple fruits cultivated in rural and peri-urban orchards. A total of 111 fungal gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
36
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 92 publications
(139 reference statements)
8
36
0
1
Order By: Relevance
“…In our study, seven fungal taxa, i.e., Chaetomium , Coprinellus , Acremonium , Fusarium , Aspergillus , Sordariomycetes, and Plectosphaerellaceae, were abundantly found in the soil, which was consistent with earlier reports [12,45]. However, analyses confirmed that soil chemical properties and RGS treatments were decisive factors altering the fungal community in the soil.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, seven fungal taxa, i.e., Chaetomium , Coprinellus , Acremonium , Fusarium , Aspergillus , Sordariomycetes, and Plectosphaerellaceae, were abundantly found in the soil, which was consistent with earlier reports [12,45]. However, analyses confirmed that soil chemical properties and RGS treatments were decisive factors altering the fungal community in the soil.…”
Section: Discussionsupporting
confidence: 92%
“…Clusters of orchard-specific genera were found in the heatmap of fungal relative abundance (Supporting Information Fig. S8A) and taxa known to be affected by geographical location, such as Eurotiomycetes, Pleosporales and Davidiella; (Bokulich et al, 2014;Shen et al, 2018), differed in relative abundance between orchard 1 and Fig. 2.…”
Section: Orchard Location Affected the Taxonomic Structure And Tempormentioning
confidence: 99%
“…Microbial ecology is increasingly focussing attention on factors that can influence the composition of plant-associated microbial communities (Busby et al, 2017) and their possible negative or positive effects on plant hosts (Mendes et al, 2013). In particular, environmental conditions (Bokulich et al, 2014;Shen et al, 2018), tissue age (Vorholt, 2012;Arrigoni et al, 2018) and plant genotype (Correa et al, 2007;Whipps et al, 2008;Arrigoni et al, 2018) are key determinants of the microbiota taxonomic structure. For example, geographical location influences the structure and the composition of fungal and bacterial communities associated with grapevine (Bokulich et al, 2014;Perazzolli et al, 2014;Mezzasalma et al, 2017;Vitulo et al, 2019) and lettuce (Rastogi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Rinsing by shaking at 120 rpm for 20 min Plating [28] Water and phosphate buffer, pH 6.5 Rinsing first time in water; and once with sonication bath with phosphate buffer Plating [29] No buffer Wiping the fruit surface with moistened cotton swab Amplicon sequencing [30,31] Phosphate buffer, pH 6.8…”
Section: Applementioning
confidence: 99%